Digital Literacy Governance Management in SMA Negeri Sumatera Selatan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The objective of this research is to find out the implementation of digital literacy governance management in Senior High school. This research is qualitative case study method. The result shows that management of digital literacy governance in SMA Negeri Sumatera Selatan is conducted through four management functions which are planning, organizing, actuating and controlling. Planning process described by research, meetings, proposal design, and policy determination. The forming of committee for SMA Rujukan program performs the organizing process. The actuating process shown by the implementation of digital literacy strategies formulated by Indonesia Ministry of Education and Culture. The controlling process is not applied to all teachers, staff and students but can be seen through the supervision and evaluation of SMA Rujukan program, teacher’s supervision, and survey’s result of library and IT divisions from students.